Numerical solution for boundary layer flow of a dusty micropolar fluid due to a stretching sheet with constant wall temperature - Dasman, Anisah; Mohd Kasim, Abdul Rahman; Waini, Iskandar; Khashi’ie, Najiyah Safwa (Penerbit Akademia Baru, 2021)
This paper aims to present the numerical study of a dusty micropolar fluid due to a stretching sheet with constant wall temperature. Using the suitable similarity transformation, the governing partial differential equations for two-phase flows of the fluid and the dust particles are reduced to the form of ordinary differential equations. The ordinary differential equations are then numerically analysed using the bvp4c function in the MATLAB software. The validity of present numerical results was checked by comparing them with the previous study. The results graphically show the numerical solutions of velocity, temperature, and microrotation distributions for several values of the material parameter K, fluid-particle interaction parameter β and Prandtl number for both fluid and dust phase. The effect of microrotation is investigated and analysed as well. It is found that the distributions are significantly influenced by the investigated parameters for both phases.